“Elaboración de un Proyecto de Factibilidad para la implementación de una empresa textil productora y comercializadora de vestidos para mujeres tallas plus (tallas grandes), de la ciudad de Loja - Cuenca Carrión, Maura Jhoselyn (2017)
The present research project has the purpose of demonstrating the feasibility of the company for the implementation of a textile company that manufactures and sells clothing for women of size plus of the city of Loja, in order to put into practice the knowledge acquired, in Favor of a society that needs new entrepreneurs. The general objective of the research work is to determine the preparation of a feasibility project for the implementation of a textile company that produces and sells clothing for women plus sizes (large sizes), from the city of Loja; In which the four main studies of the project that determined its feasibility have been carried out. In order to carry out the objective, research methods were used as the deductive method to review the theoretical references, the inductive method to conclude with the profitability of the project, the statistical method, served to represent, simplify and analyze the data obtained, and The Descriptive - Analytical method was used during the development of the research, and the collection of the necessary information for the elaboration of the project was carried out. Techniques such as direct observation and the survey were also applied through the segmentation of the market, Considering the population of women aged 15 to 64 years of the city of Loja, according to data from the National Institute of Statistics and Censuses in 2010 is 58,735 inhabitants, with a growth rate of 2.65%, which was performed A sample size that resulted from 382 surveys to be applied to said segmentation, in the same way 2 88 surveys obtained from a total of 1141 locations according to data from the Internal Revenue Service of 2016. In the discussion we conducted the market study where we established the potential demand for the first year is 52,223 which represents 76%, the real demand is 40,241 for the first year which means 77%, the effective demand in units for The first year of 60,344 size plus dresses and the unsatisfied demand is 51,128 plus size dresses. The technical study details the size; Where the capacity used is 80% of the installed capacity, producing 4,992 dresses for women plus size, having a market share of 9.76%, the macro and micro location of the company will be in 5 the canton and city of Loja, Citadel the Immaculate, streets, Av. Salvador Bustamante Celi, Francisco Rhodes, obtaining the size of the plant of 1115 m2. In the administrative and legal study, this company is legally constituted as a Limited Liability Company and its name will be: "CASA PLUS XX" EURL; Organizational charts and function manuals are presented. In the financial study the project reaches an initial investment of $ 42,622 dollars, and will be financed with an internal contribution that is 53.08% of the total investment corresponding to $ 22,622 and a loan that will maintain the project with the bank Loja which is 46.92% which corresponds to $ 20,000 dollars at an interest rate of 11.50%. As for the financial evaluation, it is worth mentioning that the project is feasible since it has a positive Net Present Value (NPV) of $ 42,721.01, which indicates that the project or investment is convenient. For the present project, the Internal Rate of Return (IRR) is 43.86%, and this value is satisfactory for the project, in terms of the Cost / Benefit Ratio (RB / C) is $ 1.33, It follows that for every dollar invested the company will have a profit of 33 cents, the Capital Recovery Period (PRC) is 2 years, 1 month and 2 days while the sensitivity analysis determined that the company supports an increase of up to 13.36% in its costs giving a total of 0.99; And a decrease of 10.09% in their income giving a total of 0.99 so that the project is feasible. In the conclusions it was determined that the project is feasible according to the results obtained, because there are a lot of women who are size plus and can not find their garments with ease (pág. 157). In the recommendations are made of agreements to the results obtained so that in case of creating the company maximizes the risks, attaching the bibliography consulted with their respective annexes.